The presence of San Fernando in our medals - Álvarez, Ricardo (2008)
San Fernando Medical Faculty is not only the oldest medical school in our country, but also one of the few Peruvian institutions that can boast of a close to two hundred years continuous existence. Throughout an extended institutional life in a country with rich and long medals minting tradition, it is to be expected that some of its main events have been recalled for posterity by commemorative medals. Thanks to that branch of numismatics dealing with the minting and study of medals we can allow Peruvian public and San Fernando alumni in particular to learn on this fascinating subject as well as keeping a written record for the future.